Multidimensional Integrative Genomics Approaches to Dissecting Cardiovascular Disease - Arneson, Douglas; Shu, Le; Tsai, Brandon; Barrere-Cain, Rio; Sun, Christine; Yang, Xia (Frontiers in Cardiovascular Medicine, 2017)
Elucidating the mechanisms of complex diseases such as cardiovascular disease remains a significant challenge due to multi-dimensional alterations at molecular, cellular, tissue, and organ levels. To better understand cardiovascular disease and offer insights into the underlying mechanisms and potential therapeutic strategies, data from multiple omics types (genomics, epigenomics, transcriptomics, metabolomics, proteomics, microbiome) from both humans and model organisms has become available. However, individual omics data types capture only a fraction of the molecular mechanisms. To address this challenge, there have been numerous efforts to develop integrative genomics methods which can leverage multi-dimensional information from diverse data types to derive comprehensive molecular insights. In this review, we summarize recent methodological advances in multi-dimensional omics integration, exemplify their applications in cardiovascular research, and pinpoint challenges and future directions in this incipient field.